Microplasma direct writing for site-selective surface functionalization of carbon microelectrodes - Thiha, Aung; Ibrahim, Fatimah; Muniandy, Shalini; Madou, Marc J. (Springer Nature, 2019)
Carbon micro- and nanoelectrodes fabricated by carbon microelectromechanical systems (carbon MEMS) are increasingly used in various biosensors and supercapacitor applications. Surface modification of as-produced carbon electrodes with oxygen functional groups is sometimes necessary for biofunctionalization or to improve electrochemical properties. However, conventional surface treatment methods have a limited ability for selective targeting of parts of a surface area for surface modification without using complex photoresist masks. Here, we report microplasma direct writing as a simple, low-cost, and low-power technique for site-selective plasma patterning of carbon MEMS electrodes with oxygen functionalities. In microplasma direct writing, a high-voltage source generates a microplasma discharge between a microelectrode tip and a target surface held at atmospheric pressure. In our setup, water vapor acts as an ionic precursor for the carboxylation and hydroxylation of carbon surface atoms. Plasma direct writing increases the oxygen content of an SU-8-derived pyrolytic carbon surface from ~3 to 27% while reducing the carbon-to-oxygen ratio from 35 to 2.75. Specifically, a microplasma treatment increases the number of carbonyl, carboxylic, and hydroxyl functional groups with the largest increase observed for carboxylic functionalities. Furthermore, water microplasma direct writing improves the hydrophilicity and the electrochemical performance of carbon electrodes with a contact-angle change from ~90° to ~20°, a reduction in the anodic peak to cathodic peak separation from 0.5 V to 0.17 V, and a 5-fold increase in specific capacitance from 8.82 mF∙cm−2 to 46.64 mF∙cm−2. The plasma direct-writing technology provides an efficient and easy-to-implement method for the selective surface functionalization of carbon MEMS electrodes for electrochemical and biosensor applications. © 2019, The Author(s).